Identification and Prediction of Allo-Source Overpressure Caused by Vertical Transfer: Example from an HTHP Gas Reservoir in the Ledong Slope in the Yinggehai Basin. (27th April 2021) - Fan, Caiwei; Xu, Changgui; Li, Chao; Liu, Aiqun; Li, Hu; Hou, Jingxian; Zhang, Xiaoying; Lu, Bin; Li, Jun
Abstract : The Yinggehai Basin is a typical high temperature and high pressure (HTHP) gas-bearing basin. The pressure coefficient exceeds 2.2 in deeply-buried Miocene reservoirs in the Ledong Slope, a nondiapir zone in the Yinggehai Basin. Determining the overpressure mechanisms and predicting the pore pressure are key issues for natural gas exploration and development in the Ledong Slope. In this paper, overpressure mechanisms were investigated according to the analysis of vertical effective stress-logging responses and geological evaluations, and the pore pressure was predicted using the Bowers method. The loading-unloading crossplots indicated that the overpressure that existed in reservoirs mainly consists of two types: neighbor-source and allo-source overpressure. The neighbor-source overpressure is mainly caused by the pressure transmission from the adjacent mudstone to the reservoir, with a pressure coefficient less than 1.5 1.6. The high-magnitude overpressure points with pressure coefficients greater than 1.6 show a typical unloading response, indicating elevated sandstone pressures rather than in situ mudstone pressures, which are most likely to be generated by overpressure vertical transfer. The high-magnitude overpressure fluid generated by the high mature ultradeep buried N1 s source rock migrated to the shallower reservoirs via hidden faults/microfractures, which led to the vertical transfer of overpressure. Vertically transferred overpressure was generated at 1.5 0.2 Ma, which is beneficial for the preservation of overpressure in lenticular sandbodies. The estimated pore pressure by the Bowers method is in good agreement with the measured pressure and provides a meaningful reference for predrilling pressure prediction in nondiapir or diapir zones in the Yinggehai Basin.